Impact of religiosity towards organizational commitment:a case of banking institutions in Mukah / Siti Farah Lajim … [et.al.]. - Lajim, Siti Farah; Bohari, Mohamad Musa; Shamsuddin, Noor Emma (2016)
The purpose of this paper is to determine the relationship between religiosity and organizational commitment among employees currently working in banking institutions in Mukah area. In addition, this study also attempts to assess the level of religiosity and organizational commitment. In addition, the study is also conducted to make improvements on issues of employees' religiosity in a company. 63 data were collected using available structured questionnaire from eight banking institutions in Mukah and analyzed using SPSS. The findings of the study indicated that there were statistically significant positive relationships between intrinsic religiosity and organizational commitment however, there was no significant relationship found between extrinsic religiosity and organizational commitment. Therefore, only intrinsic religiosity component had a strong impact on organizational commitment.